FORMULASI DAN EVALUASI KESTABILAN FISIK SEDIAAN MASKER GEL PEEL-OFF DARI SARI BUAH LEMON CUI (Citrus microcarpa Bunge.) - Arifin, Arfiani; Sartini, Sartini; Suwitno, Nurmadani (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2023)
Lemon cui also known as fish lemon or kalamansi lemon is known to contain one of them vitamin C which has the potential as an antioxidant so that it can be applied as active ingredient in peel off mask preparations. The aims of this study weretoobtaining the best PVA concentration in the manufacture of peel-off gel masks from lemon cui juice that meet the stability test requirements. physique. The method of making a sample of lemon cui juice is obtained by grinding it using a blender, adding 100 mL of water and then separating the pulp to obtain the juice. The formulation of peel-off gel mask preparations uses variations in the concentration of PVA (Polyvinyl Alcohol), namely F1 (10%), F2 (13%) and F3 (16%). Physical stability tests included organoleptic tests, homogeneity tests, spreadability tests, pH tests, adhesion tests and drying time tests.The results showed that the preparations F1, F2 and F3Â  showed physical stabilityÂ  based on the results of organoleptic tests, homogeneity tests, spreadability tests, pH tests, adhesion tests and drying time tests before and after accelerated storage conditions. Based on the test results obtained, it can be concluded that the formulation of the Lemon Cui peel-off gel mask preparation from the three concentrations of PVA met the requirements for physical stability. The best PVA concentration is 10% because it has the best dry time.